Oncolytic Viruses: The Best is Yet to Come - G. Lemay, Chantal; A. Keller, Brian; E. Edge, Robert; Abei, Masato; C. Bell, John (Current Cancer Drug Targets, 2018)
Oncolytic viruses are a promising anti-cancer platform, achieving significant pre-clinical and clinical milestones in recent years. A full arsenal of selective, safe, and effective viruses has been developed with some emerging pre-clinical research focusing on optimizing these therapies in the face of remaining challenges, both in the bloodstream and in the tumour microenvironment. Herein we discuss the recent progress in pre-clinical virotherapy research to address these challenges, with special focus on innovative strategies that seek to complement the current strengths of virotherapy, ensuring an optimal multi-faceted attack on cancer. This review highlights the research areas that we believe provide the most potential to increase the efficacy of this exciting biotherapy platform: cell carriers, tumour vascular destruction, microenvironment modulation, combination therapies, and virus-mediated anti-tumour immune responses.
Keywords: oncolytic viruses